Advancements in Image Classification and Object Detection: Leveraging Deep Learning for Enhanced Performance - Bheesetty Srinivasa Rao (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper summarizes the research focusing on image classification and object detection. For object detection, we addressed the challenge of bridging deep convolutional neural networks (CNNs) with traditional detection frameworks to achieve accurate and efficient generic object detection. We introduced Dense Neural Patterns (DNPs), dense local features derived from discriminatively trained deep CNNs, which demonstrated effectiveness in the Regionlets detection framework, significantly improving performance on the PASCAL VOC datasets. In image classification, key advancements include the development of Latent CNN for handling multi-label images, Multiple Instance Learning Convolutional Neural Networks (MILCNN) for leveraging deep learning with limited labeled data, and the Residual Networks of Residual Networks (RoR) architecture for enhancing optimization. Despite these contributions, there remains room for improvement: enhancing detection speed through CNN-generated bounding box proposals, incorporating unsupervised learning to align with natural learning processes, and employing RNNs with LSTM units for generating more effective image regions in classification tasks.